BRIEF NOTE ON THE PROXIMATE COMPOSITION OF SILVERBELLIES OF PORTO NOVO WATERS - Jayabalan, N; Ramamoorti, K (Indian Journal of Fisheries, 2011)
Proximate composition of ten species of leiognathids was studied fromnutritive point of view; In the dried samples of flesh of these species, proteinvaried betvsreen 73.87% and 77.07%; fat between 2.96% and 5.98%; and carbohydratebetween 0.75% and 2.06%. The ash value ranged from 17.17% to22.64% and the moisture content correspondingly from 73.67% to 77.40%.